Mexico’s opinion in Managua-Washington Case of 1909 - Pérez Reyes, Elda (Acta Scientiarum Socialium, 2011)
Mexico’s opinion in Managua–Washington Case of 1909. The guiding axis of the present article is the analysis of the position of the Mexican foreign policy and the representations and the news of the newspaper of cut pro-government official, El Imparcial one, against the Managua-Washington disagreement of end of 1909. In this way we try to demonstrate that: the Mexican chancellery used moralistic resources as a last resort to take part in favor of José Santos Zelaya in front of the United States and use the political asylum as a last resort. Therefore, the operators of the porfirista diplomacy warily assumed cautious policies when conducting itself in the objective triple of: out of danger to put its bows with the Department of State, to denounce the interventionism of this one and to support to Zelaya. The article will be based on primary sources, the heaps of the Archivo Histórico Genaro Estrada de la Secretaría de Relaciones Exteriores de México and on El Imparcial, the official daily.